ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY PADA PERUSAHAAN SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2023 - Ali, Amrullah Imran Hakim; Andreas, Andreas; Sinta, Ramaiyanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This research is motivated by the fact that industrial companies experienced delays insubmitting audit financial statements during 2019 to 2023 having a significant averagegrowth compared to other companies, which was 194%. This study aims to find out howto analyze the factors that affect audit delays in companies in various industry sectorslisted on the Indonesia Stock Exchange for the 2019-2023 period. The type of data usedin this study is quantitative data. The data source used in this study is a secondary datasource. The results of the study show that the size of the company has no effect on auditdelay. These results show that the variation in the size of the company does not affect theduration of the completion of the audit. This is due to the relatively uniform size of thecompanies in this study which indicates that the size of the companies in the sample doesnot have any noticeable differences. Profitability affects audit delays. The higher thecompany's profitability level, the faster the audit will be completed. This is becauseprofitable companies want to announce positive financial results faster and want to havethe right resources and financial systems in place to support efficient audit procedures.The duration of the audit affects the delay of the audit. The longer the auditor'srelationship with the company, the faster the audit will be completed. Auditors have abetter understanding of the company's operational and financial systems and enable themto carry out audits more efficiently. Although in theory an opinion other than a fairopinion without exception could lead to an extension of the audit period, the study foundthat most companies have received a fair opinion without exception (WTP) in the last fiveyears. Ta. Therefore, it is considered that the difference in audit opinions presented inthis study is very small and does not have a significant impact on the audit period.Creditworthiness affects audit delays. The higher the debt-to-asset ratio of a company,the longer it will take to complete the audit. This is because if the company has a highlevel of debt, the auditor needs to conduct an in-depth analysis of the company's survivaland compliance with financial obligations.Keywords: Audit Delay, IDX, Company, Industry)